The Traumatic brain injuries in sports - neurological aspects - Adrianna Marta Paziewska; Karolina Jurasz; Radosław Cymer; Ewa Rzeska; Michał Rogulski (Kazimierz Wielki University, 2024)
Traumatic Brain Injury (TBI) was characterized  as alternation in brain function or any other sign of brain pathology resulting from external force. Sport-related traumatic brain injury (SR-TBI) calculated as up to 20% of all TBA. Different diagnostic tools, such as CT scan or MRI, are utilized in clinical assessment of the patients, however there is a necessity of further investigation of new diagnostic methods such as biomarkers. A long-term repetitive brain injury can lead in consequence to a Chronic Traumatic Encephalopathy (CTE). Neuroprotection, treatment  and rehabilitation play a crucial role in both prevention and recovery of TBI patients.